A Lethal Aerosol Exposure Model of Nipah Virus Strain Bangladesh in African Green Monkeys. (30th October 2019) - Prasad, Abhishek N; Agans, Krystle N; Sivasubramani, Satheesh K; Geisbert, Joan B; Borisevich, Viktoriya; Mire, Chad E; Lawrence, William S; Fenton, Karla A; Geisbert, Thomas W
Abstract: The high case-fatality rates and potential for use as a biological weapon make Nipah virus (NiV) a significant public health concern. Previous studies assessing the pathogenic potential of NiV delivered by the aerosol route in African green monkeys (AGMs) used the Malaysia strain (NiVM ), which has caused lower instances of respiratory illness and person-to-person transmission during human outbreaks than the Bangladesh strain (NiVB ). Accordingly, we developed a small particle aerosol model of NiVB infection in AGMs. Consistent with other mucosal AGM models of NiVB infection, we achieved uniform lethality and disease pathogenesis reflective of that observed in humans.